PEMANFAATAN IOT UNTUK MENINGKATKAN PRODUKTIVITAS DAN HASIL PENJUALAN CABAI ORGANIK SRITANIO - Windha MP Dhuhita; Uyock Anggoro Saputro; Rivga Agusta; Aryo Bimo Wicaksono; Rizka Nanda Salsabila (Jurnal Abdi Insani, 2023)
The SriTanio youth farming group, chaired by Tantra Gumilar, was founded in 2021 with the concept of creating sustainable organic farming by utilizing technological developments. However, the location of the agricultural land does not have access to electricity and is far from residential areas. So chili plant care is currently carried out conventionally, including irrigation and pest control. Farmers only estimate the intensity of watering. Currently, conventional methods are still used to control pests by making herbal pesticides made from herbs to repel insects without being able to break the life cycle of adult insects that disturb plants. The Community Partnership Program (PKM) is aimed at the SriTaniO group in nggul Arum village, Turi Sleman Yogyakarta. This PKM program applies the use of IoT and solar panels to increase the productivity of organic agricultural products. In monitoring plant growth, sensors for soil moisture, temperature and light intensity are needed. Plus the use of plant pest insect traps. This activity also opens up training opportunities for farmers and local youth who are interested in organic farming. In this activity, they share their organic farming knowledge and technology, so that the productivity and quality of their agricultural products increases. This PKM program applies the use of IoT and solar panels to increase the productivity of organic agricultural products. The output of this activity includes a solar panel system on agricultural land, the availability of an IoT-based land condition monitoring and automatic irrigation system as well as an IoT-based Pest Control System. With this system, farmers can monitor land moisture conditions at any time. So, by using IoT technology in the process of caring for and producing chili plants on land far from access to electricity, harvest yields can be maximized.